FAKTOR PENYEBAB KEDISIPLINAN PESERTA DIDIK KELAS TINGGI DI SD NEGERI 11 ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Guslianda, Bobby; Helma, Helma; Zaini, Ahmad (Bimbingan dan Konseling, 2014)
This research is based on the discipline problem of a great many students at school either by the school regulation or studying and teaching process. The purpose of this research is the describe: 1) School factors causing discipline problem towards high class students in elementary school number 11 Alahan Panjang,2) Family Factors causing discipline problem towards high class students in Elementary School number 11Alahan Panjang. The research type is descriptive. The research population is the high class students namely from the fourth until the sixth class in Elementary School Number 11 Alahan Panjang with the amount of 120 students. The sample taking uses proportional stratified random sampling method. The amount of sample is 36 students.The instrument used to collect data is questionnaire. The technique used to analyze data is percentage technique. The research result shows that the factors causing students discipline in the category of discipline have the percentage of 75% out of 36 respondents, the category of very discipline is 25% out of 36 respondents whereas the category of fair discipline, less discipline and not discipline is none of the respondents. The research result is recommended among other for the students in order to keep and improve discipline, for the teachers in order to increase studentsâ discipline, for the department of guidance and counseling as the input in developing subjects related to studentsâ discipline and the next researcher interested in the same matter in order to relate it with another variables.Â Â